Chronic inflammation, cancer development and immunotherapy - Wen, Yalei; Zhu, Yingjie; Zhang, Caishi; Yang, Xiao; Gao, Yuchen; Li, Mei; Yang, Hongyan; Liu, Tongzheng; Tang, Hui (Frontiers in Pharmacology, 2022)
Chronic inflammation plays a pivotal role in cancer development. Cancer cells interact with adjacent cellular components (pro-inflammatory cells, intrinsic immune cells, stromal cells, etc.) and non-cellular components to form the inflammatory tumor microenvironment (TME). Interleukin 6 (IL-6), macrophage migration inhibitory factor (MIF), immune checkpoint factors and other pro-inflammatory cytokines produced by intrinsic immune cells in TME are the main mediators of intercellular communication in TME, which link chronic inflammation to cancer by stimulating different oncogenic signaling pathways and improving immune escape to promote cancer development. In parallel, the ability of monocytes, T regulatory cells (Tregs) and B regulatory cells (Bregs) to perform homeostatic tolerogenic functions is hijacked by cancer cells, leading to local or systemic immunosuppression. Standard treatments for advanced malignancies such as chemotherapy and radiotherapy have improved in the last decades. However, clinical outcomes of certain malignant cancers are not satisfactory due to drug resistance and side effects. The clinical application of immune checkpoint therapy (ICT) has brought hope to cancer treatment, although therapeutic efficacy are still limited due to the immunosuppressive microenvironment. Emerging evidences reveal that ideal therapies including clearance of tumor cells, disruption of tumor-induced immunosuppression by targeting suppressive TME as well as reactivation of anti-tumor T cells by ICT. Here, we review the impacts of the major pro-inflammatory cells, mediators and their downstream signaling molecules in TME on cancer development. We also discuss the application of targeting important components in the TME in the clinical management of cancer.